Kadar Cholinesterase dalam Darah Petani di Dusun Taeno, Kecamatan Teluk Ambon, Kota Ambon - Samuel Titaley; Gracia Victoria Souisa (2-TRIK: TUNAS-TUNAS RISET KESEHATAN, 2021)
A vegetable farmer group in Taeno Hamlet, Teluk Ambon District, Ambon City uses pesticides in farming. Based on interviews with farmer extension agents, the use of pesticides in Taeno Hamlet was not in accordance with regulations. Farmers also do not realize the importance of using PPE when applying pesticides and do not understand the correct attitude / method when spraying. One indicator to monitor pesticide poisoning of farmers is blood cholinesterase testing. The purpose of this study was to determine the levels of Cholinesterase in the blood of farmers using pesticides in Taeno Hamlet, Teluk Ambon District, Ambon City. The research method used was descriptive with laboratory testing. Cholinesterase examination will be carried out in Prodia's laboratory. The population in this study were 15 farmers in the "Taeno Mekar" group. The results showed that the cholinesterase levels in the farmers' blood were still in the normal category, namely at levels 8,287 - 12,167 U / L where the normal values were 4,260 - 11,250 U / L for ages <40 years and 5,320 - 12,920 U / L for ages ≥40 years.Keywords: cholinesterase; farmers; Taeno hamletABSTRAK Kelompok tani sayuran di Dusun Taeno, Kabupaten Teluk Ambon, Kota Ambon menggunakan pestisida dalam bertani. Berdasarkan wawancara dengan penyuluh petani, penggunaan pestisida di Dusun Taeno tidak sesuai dengan ketentuan. Petani juga tidak menyadari pentingnya menggunakan APD saat mengaplikasikan pestisida dan tidak memahami sikap / cara yang benar saat menyemprot. Salah satu indikator untuk memantau keracunan pestisida pada petani adalah pengujian kolinesterase darah. Tujuan penelitian ini adalah untuk mengetahui kadar Kolinesterase dalam darah petani pemakai pestisida di Dusun Taeno, Kecamatan Teluk Ambon Kota Ambon. Metode penelitian yang digunakan adalah deskriptif dengan pengujian laboratorium. Pemeriksaan kolinesterase akan dilakukan di laboratorium Prodia. Populasi dalam penelitian ini adalah 15 orang petani di kelompok "Taeno Mekar". Hasil penelitian menunjukkan bahwa kadar kolinesterase dalam darah petani masih dalam kategori normal yaitu pada kadar 8.287 - 12.167 U / L dimana nilai normalnya adalah 4.260 - 11.250 U / L untuk umur <40 tahun dan 5.320 - 12.920 U / L untuk usia ≥40 tahun.Kata kunci: cholinesterase; petani; dusun Taeno